UJI AKTIVITAS ANTIMIKROBA EKSTRAK ETANOL DAUN SELASIH (Ocimum Basilicum L.) TERHADAP PERTUMBUHAN Streptococcus mutans Dan Candida albicans - inelvi yulia; Eliza Arman (Stikes Syedza Saintika Padang, 2023)
Basil (Ocimum basilicum L.) is a plant that contains several bioactive compounds such as eugenol, methyl eugenol, metal cinnamate, methylchavicol and others which are found mostly in the leaves. Basil plants are widely used for traditional medicine and as an antimicrobial. The purpose of this study was to determine the antimicrobial activity of basil leaves against Streptococcus mutans and Candida albicans in vitro. The method used is a laboratory experimental quantitative method. Basil leaves ethanol extract with concentrations of 100%, 90%, 80%, and 70% Amoxicilin trihydrate as positive control and DMSO as negative control. The results showed that the ethanol extract of basil leaves could inhibit the growth of C.albicans and was categorized as having moderate inhibition, whereas S. mutans had strong inhibition. In statistical tests using ANOVA, significant results were obtained > 0.05, indicating that differences in concentrations of ethanol extract of basil leaves did not have the same effect on the growth of Candida albicans and Streptococcus mutans.